SARS-COV-2 causes significant abnormalities in the fibrinolysis system of patients: correlation between viral mutations, variants and thrombosis - Abudouleh, Esra’a; Owaidah, Tarek; Alhamlan, Fatimah; Al-Qahtani, Arwa A.; Aljowaie, Reem M.; Al-Ghnnam, Fatimah; Fe Bohol, Marie; Al-Qahtani, Ahmed A. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCoronavirus disease (COVID-19) is reported as a complex disorder affecting multiple systems and coagulopathy that can cause mortality. In this study, we investigated the correlation of SARS-CoV-2 mutations found in blood samples with various changes in the fibrinolysis system, as well as the severity of the disease based on outcome and whether or not these patients were admitted into the ICU.Materials and methodsCOVID-19 patients (n = 446) admitted to our institute between 2021 and 2022 were recruited. Blood samples were collected, and a sequence analysis of the SARS-CoV-2 spike gene was isolated from the blood. Measured several parameters of fibrinolysis and coagulation, including alpha-2-antiplasmin and plasminogen, thrombin activatable fibrinolysis inhibitor (TAFI), tissue plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), D-dimer, and fibrinogen levels.ResultsSARS-CoV-2 RNA was found in 123/446 (27.6%) of the blood samples. The N501Y, D614G, K417N, and P681R mutations among COVID-19 patients were associated with higher admissions to the ICU (P = 0.0057, P = 0.0068, P = 0.0193, and P = 0.018, respectively). Omicron (BA.1.1) variant variants are highly associated with thrombosis (P = 0.002) in hospitalized COVID-19 patients that are unvaccinated and have comorbidity conditions. The plasma levels of tPA, aPTT, and D-dimer were significantly higher in participants who had the N501Y mutation (P = 0.044, P = 0.024, and P = 0.027, respectively).ConclusionThrombosis was the most prevalent condition among severe COVID-19 patients. The correlation between specific SARS-CoV-2 new variants and thrombosis warrants more investigation.